Extraneural metastases in medulloblastoma - V M F Muoio; S O Shinjo; H Matushita; S Rosemberg; M J Teixeira; S K N Marie (Arquivos de Neuro-Psiquiatria)
Medulloblastoma is the most common childhood malignant tumor of central nervous system, but it may also occur in adults. It presents high invasive growth with spreading of tumor cells into the leptomeningeal space along the neuroaxis early in the course of the disease. Extraneural metastases are rare but frequently lethal, occurring only in 1 to 5% of patients, and are related, in the most of cases, to the presence of ventriculoperitoneal shunt. Here we characterize the clinical profile of five cases of medulloblastoma with systemic spreading of tumor cells, also comparing them to cases already described in the literature.